REAL-TIME LOGISTICS - Case Development of a Shipment Status Display System for a Large Manufacturing Company - Ta, Hieu (My University, 2013)
As traditional heavy industry businesses transform into global solutions providers, their business models change into project-based and their supply networks expand. Project business faces greater uncertainty within the supply chain than traditional business, thus requires greater need for data exchange within the supply chain. Numerous information systems have provided the organization with a wealth of data. However project management often faces great challenges to utilize it for better visibility on project delivery status, as well as to communicate that to stakeholders. In response to the need for better usage and presentation of transactional project logistical data, a real-time shipment status display system has been developed. The complete system offers an intuitive, up-to-date, fast, and reliable display that is accessible through a wide range of devices. In this thesis, the system is customized to run on public displays. In term of development methodology, spiral axiomatic design approach is adopted to ensure maximum independence of components. The end result is a system comprising of two independent sub-systems: one is for data collection and the second one is for presentation. Modern web technologies such as ASP.NET MVC4, HTML5, and CSS3 have been used to develop the presentation sub-system. The thesis contributes a software artifact that complements information systems that are either too much focused on transactional data or unable to communicate project logistics data to stakeholders. It also demonstrates the use of axiomatic system design in developing modern web platforms.
Keywords: real-time logistics display; axiomatic design; project logistics information system; LogTrack; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|